The Influence of COD (Cash On Delivery), ShopeePay, and Virtual Account Payment Methods on Purchasing Decisions on the Shopee Marketplace - Mavira, Sherli; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2025)
Research objective: This study aims to determine and analyze the influence of Cash On Delivery (COD), ShopeePay , and virtual account payment methods on purchasing decisions in the marketplace. Shopee either partially or simultaneously. Design/Method/Approach: The approach in this study uses a quantitative approach with a causality research type. The population of this study were students of the Faculty of Economics and Business, Nusantara PGRI University, Kediri who had made purchases on the marketplace. Shopee at least five times. The sample used in this study was 40 respondents taken using purposive sampling technique. The data analysis technique used multiple linear tests. Research Findings: The results of this study indicate that the cash payment method on delivery ( cod ) and ShopeePay have a significant effect on purchasing decisions and the virtual account payment method does not have a significant effect on purchasing decisions. However, these three variables have a partial and simultaneous effect on purchasing decisions. Theoretical contribution/Originality: This study contributes to understanding and providing insights related to COD, ShopeePay , and virtual account payment methods to reach purchasing decisions. Implications for Practitioners/Policies: This study provides practical implications for business actors (other than Shopee ) to provide convenience through payment methods that influence consumer purchasing decisions. Research limitations: The limitation of this research is that the research variables only focus on payment methods.